1979
DOI: 10.1017/s0022029900017611
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes of psychrotrophic bacteria and their effects on milk and milk products

Abstract: B. A. LAW lipases (including phospholipases) which, because they are produced extracellularly, can act directly on micellar casein and on the fat globules in milk. They can act in raw milk while it is being stored and the psychrotrophs are multiplying, but they may also continue to act in heat-treated liquid milk and other products. PROTEINASES OF PSYCHROTROPHIC BACTERIA Proteinase-producing groups Some thermoduric bacteria are well known for their ability to produce extracellular proteinases (e.g. Priest, 197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0
5

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(114 citation statements)
references
References 74 publications
1
108
0
5
Order By: Relevance
“…Dans D. Pâque! une revue, Law (1979) rapporte l'effet de ces bactéries sur les constituants du lait. D'autres protéases d'origine leucocytaire apparaissant dans la mammelle des animaux atteints de mammite peuvent être responsables de l'hydrolyse des protéines (Grieves et Kitchen, 1985) et, par conséquent, d'une modification du taux de protéose-peptones.…”
Section: Evolution De La Fraction Protéose-peptones Dans Le Laitunclassified
“…Dans D. Pâque! une revue, Law (1979) rapporte l'effet de ces bactéries sur les constituants du lait. D'autres protéases d'origine leucocytaire apparaissant dans la mammelle des animaux atteints de mammite peuvent être responsables de l'hydrolyse des protéines (Grieves et Kitchen, 1985) et, par conséquent, d'une modification du taux de protéose-peptones.…”
Section: Evolution De La Fraction Protéose-peptones Dans Le Laitunclassified
“…Lack of gelation observed in samples inoculated with Pseudomonas fluorescens 416 even after 9 days of storage gelation on day 2 with Pseudomonas fluorescens without sequesters indicates the role of the bacterial proteases to gelation. Investigation into the gelation of milk by Pseudomonas fluorescens proteinases confirmed that a gel formed depending on the activity of the organism before heat treatment ( Costa et al, 2002;Law, 1979;Law et al, 1977) ,. It was also revealed that proteases from psychrotrophic bacteria are capable of causing gelation of UHT milk (Cogan, 1977).…”
Section: It Is Obvious Formmentioning
confidence: 99%
“…lipoprotein lipase, LPL, EC 3.1.1.34). Plasmin and LPL are biochemically active at refrigeration temperatures and can cause slow degradation of milk proteins and lipids, (Law 1979). Changes in the internal constituents of raw milk during storage are mainly related to nutrient exchanges by bacteria between the inner and outer milk fractions (Baldo et al 1991).…”
Section: Introductionmentioning
confidence: 99%